An Integrated Smart Village Information System for Digital Public Services and BUMDes Marketplace in Temesi Village - Made Junindra Maha Arta Sang; I Gede Aris Gunadi; Gede Rasben Dantes (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
The digital transformation of village governance requires information systems that not only provide administrative services but also support transparency, community participation, and local economic activities. Previous village information systems mostly focused on basic administration or information publication, while integrated public services, community reporting, budget transparency, and village-owned enterprise marketplace features remain limited. This study aims to develop an integrated web-based Village Information System based on the Smart Village concept in Temesi Village, Gianyar Regency. The system was developed using the software development life cycle with the waterfall model, including requirements analysis, system design, implementation, testing, deployment, and maintenance. Data were collected through interviews, focus group discussions, and observations involving village officials and community representatives. The system was implemented using Laravel, MySQL, and a model-view-controller architecture. The developed system provides population data management, administrative service requests, service status tracking, village information, community complaints, budget transparency, village maps, galleries, and a village-owned enterprise marketplace. Functional testing showed that the main features worked according to the expected scenarios. Usability testing involving 50 respondents, consisting of 6 information technology experts, 4 village officials, and 40 village residents, obtained an average System Usability Scale score of 86.15, categorized as Excellent. These results indicate that the system is feasible, usable, and supports Smart Village implementation in Temesi Village.